Charged-particle distributions and material measurements in ps = 13 TeV pp collisions with the ATLAS Inner Detector - Cairo, Valentina Maria Martina; Pantano, Pietro; Dell'Acqua, Andrea; Schioppa, Marco (My University, 2017)
The Run 2 of the Large Hadron Collider, which began in Spring 2015, offers new challenges to the Experiments with its unprecedented energy scale and high luminosity regime. To cope with the new experimental conditions, the ATLAS Experiment was upgraded during the first long shutdown of the collider, in the period 2013-2014. The most relevant change which occurred in the ATLAS Inner Detector was the installation of a fourth pixel layer, the Insertable B-Layer, at a radius of 33 mm together with a new thinner beam pipe. The Pixel Services, located between the Pixel and SCT detectors, were also modified. Owing to the radically modified ID layout, many aspects of the track reconstruction programs had to be re-optimized. In this thesis, the improvements to the tracking algorithms and the studies of the material distribution in the Inner Detector are described in detail, together with the improvements introduced in the geometry model description in simulation as well as the re-evaluation and the reduction of the systematic uncertainty on the estimate of the track reconstruction efficiency. The results of these studies were applied to the measurement of Charged-Particle Multiplicity in proton–proton collisions at a centre-of-mass energy of 13 TeV. The chargedparticle multiplicity, its dependence on transverse momentum and pseudorapidity and the dependence of the mean transverse momentum on the charged-particle multiplicity are presented for various fiducial phase spaces. The measurements are corrected for detector effects, presented as particle-level distributions and are compared to the predictions of different Monte Carlo event generators. New sets of recommended performance figures along with the related systematic uncertainties were also derived for several aspects of the ATLAS tracking, such as track reconstruction efficiency, fake rate and impact parameter resolution. These recommendations provide information on appropriate working points, i.e. track selection criteria with wellunderstood performance. They apply to physics analyses using Inner Detector tracks in Run 2 data and are important inputs for other objects based on tracks, such as jets. A simulation-based method which uses the tracking recommendations to calibrate light-jets mis-tagged as b-jets it is also presented in the context of the measurement of the crosssection of the W-boson produced in association with b-jets at 13 TeV, together with an overview of the inclusiveW-boson cross-section analysis.
Dottorato di Ricerca in Scienze e Ingegneria dell'Ambiente, delle Costruzioni e dell'Energia. Ciclo XXIX
Keywords: Particles physics